Cytokine activity of the non-catalytic EMAP-2-like domain of mammalian tyrosyl-tRNA synthetase - Kornelyuk, A.; Tas, M.; Dubrovsky, A.; Murray, J.C. (Биополимеры и клетка, 1999)
Cytokine activity of the isolated recombinant C-terminal domain of mammalian lyrosyl-tRNA synthetasg (TyrRS), which is homologous to a tumor-derived cytokine, endothelial and monocyte activating polypeptide (EMAP-2) has been studied. It was shown that C-domain induced a ~ 2-fold increase of monocyte chemotaxis. This effect is comparable with the values of chemotaxis induction by EMAP-2 cytokine and proEMAP-2. The truncated catalytic form of bovine TyrRS (2 x 39 kDa) lias no effect on monocyte chemotaxis. C-domain of TyrRS also induced a ~ 3-fold increase in tissue factor activity in cultured human endothelial cells. A hypothesis is forwarded that the isolated C-domain of mammalian TyrRS may be released at proteoiytic cleavage of TyrRS by some protease, activated ui stress conditions, and functions as a mediator via signal transduction through interaction with a putative EMAP-2 receptor.